The Relationship of the Level of Community Knowledge in the Family Environment with Tuberculosis Prevention Efforts - Armaita; Marni, Linda; Nisa, Setia; Lucintarillova, Bella; Aprihatin, Yessy (Postgraduate, University of Mataram, 2024)
Tuberculosis is a disease that is transmitted very quickly. One way of transmitting Tuberculosis is through droplet nuclei when a patient coughs or sneezes, especially to those closest to the patient, namely the family who lives in the same house as the patient. Poor family and community knowledge about Tuberculosis have a greater risk of increasing Tuberculosis cases, while families and communities who have good knowledge about Tuberculosis can reduce the incidence of Tuberculosis cases. To determine the relationship between the level of community knowledge and efforts to prevent tuberculosis in the Pariaman Community Health Center work area in 2022. This research is correlational with a cross-sectional study approach. that of the 48 respondents, the majority of 37 (77.10%) people had a high level of public knowledge about preventing tuberculosis. more than 35 (72.90%) people experienced good Tuberculosis Prevention Efforts. It is known that tuberculosis prevention efforts are greater among respondents who have high knowledge than respondents who have low knowledge (68.80% and 4.20%) people. Based on statistical tests using chi-square, the p-value = 0.00 (p-value < Î± 0.05) means there is a significant relationship between the level of community knowledge and efforts to prevent tuberculosis. According to the researchers' analysis, knowledge and prevention efforts must be in sync because efforts to prevent lack of knowledge do not occur well, so knowledge and prevention efforts must work well and reduce the number of TB diseases that occur. Most of the community's level of knowledge regarding tuberculosis prevention efforts. Most efforts to prevent tuberculosis are good. There is a significant relationship between the level of community knowledge and efforts to prevent tuberculosis in the Pariaman Community Health Center working area in 2022.